2014
DOI: 10.1089/hum.2013.189
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-Associated Virus Serotypes 1, 8, and 9 Share Conserved Mechanisms for Anterograde and Retrograde Axonal Transport

Abstract: Adeno-associated virus (AAV) vectors often undergo long-distance axonal transport after brain injection. This leads to transduction of brain regions distal to the injection site, although the extent of axonal transport and distal transduction varies widely among AAV serotypes. The mechanisms driving this variability are poorly understood. This is a critical problem for applications that require focal gene expression within a specific brain region, and also impedes the utilization of vector transport for applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
108
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(113 citation statements)
references
References 51 publications
5
108
0
Order By: Relevance
“…It has been reported that some AAV serotypes appear to transduce distal neurons upon cell entry via the fiber terminals in the injection site. Consequent retrograde transfer to the cell body could then result in transduced neurons several mm away (Castle et al 2014). Since this characteristic seems to depend upon the serotype and the region of interest, retrograde transfer could be limited by the use of the right serotype for the application (Aschauer et al 2013;Cearley and Wolfe 2006;Van der Perren et al 2011;Taymans et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that some AAV serotypes appear to transduce distal neurons upon cell entry via the fiber terminals in the injection site. Consequent retrograde transfer to the cell body could then result in transduced neurons several mm away (Castle et al 2014). Since this characteristic seems to depend upon the serotype and the region of interest, retrograde transfer could be limited by the use of the right serotype for the application (Aschauer et al 2013;Cearley and Wolfe 2006;Van der Perren et al 2011;Taymans et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Reports about retrograde transduction by AAV vector appear inconsistent; it has been reported as weak or ineffective in some cases (51,52) and effective in others (44,45). In addition to this inconsistency, AAV serotypes 8 and 9, which are known to undergo retrograde axonal transport, also anterogradely transduce second-order neurons in vivo (53). This anterograde transport of AAV vector is not suitable for pathway-specific gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…AAV5 and AAV8 have been demonstrated in a multitude of studies to effectively transduce neurons of these brain areas (Aschauer et al, 2013;Atasoy et al, 2012;Betley et al, 2015;Wang et al, 2015;Witten et al, 2010). Another important aspect to consider for experimental design is that both AAV5 and AAV8-serotypes are capable of axonal transport in both retro-and anterograde directions (Castle et al, 2014). This phenomenon, can be regulated in a dose-dependent manner.…”
Section: Viral Expression Strategiesmentioning
confidence: 99%
“…This phenomenon, can be regulated in a dose-dependent manner. For instance, by using lower doses of AAVs for transduction, axonal transport can be diminished (Castle et al, 2014). In study III, a high dose of AAV8 (600 nl per site of 3x10 12 genome copies/ml) was applied for retrograde transduction from the NAc shell to the ARC, compared to direct targeting of POMC-somas in the ARC (250 nl per site of 3x10 12 genome copies/ml).…”
Section: Viral Expression Strategiesmentioning
confidence: 99%